Thursday

October 23, 2014

October 23, 2014

Posted by **Enna** on Wednesday, April 18, 2012 at 6:16pm.

-2(2f-4)=-4(-f+2)

- algebra -
**Ms. Sue**, Wednesday, April 18, 2012 at 6:27pm-2(2f-4)=-4(-f+2)

-4f + 8 = 4f - 8

-8f = -16

f = 2

**Answer this Question**

**Related Questions**

Algebra Problem - I've gotten confunsed. Please help. Solve: 2y-a = a + 3b ____ ...

Algebra 2 - How do I solve these inequalities: e^3x>e^x-1 -6log (subscript of...

Algebra - FIND THE GCF OF THE PRODUCT (3B+6)(2B-10) SOLVE... X^2=-6X x(x+6)= 0 x...

Algebra (please help!) - Pretend the parentheses are absolute value bars. Solve...

Algebra - Solve 3x +1 < 5 or 3x +1 > 4 By saying "solve," is it asking for...

college algebra - please solve by method of substitution 0.3x-0.4y-0.33=0 0.1x...

Math - Algebra - Simplify and solve for x=2 and y=5. Please remember to group ...

Algebra II- please help! - I just cannot seem to be able to grasp the concept of...

Algebra - Please Solve: 4-x=-5 I thought the answer was -9 but that doesn't seem...

Algebra......Help Quick!! - 12a^3bc-18a^2bc^2+6a^2c, x^2+20x+36, 12x^4-8x^3-4x^2...